PENGEMBANGAN MEDIA PEMBELAJARAN CALISTUNG BERBANTUAN ANDROID UNTUK ANAK USIA DINI - Ina Rosmalita; Indri Astuti; Marmawi R (Institut Pendidikan Tapanuli Selatan, 2022)
The purpose of this study was to develop a calistung learning application for early childhood 5-6 years. The research method used is research and development (R&D). This research model uses the ADDIE development model. The results of the development of learning media in the form of an android application with APK format. Based on the results of material expert validation, it reached an average of 4.45 with the criteria of